Gelation of faba bean proteins - Effect of extraction method, pH and NaCl. (June 2020) - Langton, Maud; Ehsanzamir, Sohail; Karkehabadi, Saeid; Feng, Xinmei; Johansson, Monika; Johansson, Daniel P.
Abstract: The effect of extraction method, pH and NaCl addition on rheological properties and microstructure of heat-induced faba bean protein gels was evaluated. Gels formed at pH 7 (no NaCl) of alkaline-extracted protein had the densest and finest network structure and highest stress and strain at fracture. The high density of nodes and small pores in the protein network could contribute to those mechanical properties. In contrast, storage modulus (G′) and Young's modulus were lowest for protein gels at pH 7. The gels formed at pH 5 had high G′ and Young's modulus, whereas stress and strain at fracture were lower, especially for gels formed from alkaline-extracted protein. Gels formed at pH 5 with 2% NaCl had two types of internal gel network, caused by a change in solubility of 7S globulins. When the protein powder was dissolved in water, particle size was dependent on the extraction method, with alkaline extraction giving much larger protein particles than soaked extraction. Graphical abstract: Image 1 Highlights: Gels were coarser at pH 5, finer at pH 7, independent of extraction method and NaCl. At pH 5 and 2% NaCl, two separate protein networks within gels were formed. Large deformation related to pore size, small deformation to large particles in gel. Both extraction methods yielded similar protein composition in extracts.